Intracranial migration of silicone oil through the optic nerve post-vitrect - Quispe Huachaca, Jhonathan Percy (2019)
The intracranial migration of intraocular silicone oil is a rare complication in the treatment of complications of diabetic retinopathy. Several possible etiopathogenic mechanisms have been published to explain this phenomenon of migration. Silicone oil appears hyperdense on tomography, being a challenge to distinguish it from subarachnoid hemorrhage, highlighting the usefulness of magnetic resonance imaging. In patients with evidence of previous silicone retinopexy, the visualization of an intraventricular lesion with a chemical displacement device presents the possibility that it is a migration of the silicone oil. To present the case of a patient with a history of retinopexy with silicone oil and intense headache, identifying the migration of silicone oil in the ventricular system with tomography and resonance studies.